Who am I in the lives of children? : an introduction to early childhood education - Feeney, Stephanie; Feeney, Stephanie; Feeney, Stephanie (Upper Saddle River, N.J. : Merrill, 2010)
This supplement provides you with additional information specific to California. California has a unique structure for: teacher certification, ensuring that its state-funded child care and development programs are of the highest quality, and, easing your progress through the higher education system."
Includes bibliographical references and indexes.
Keywords: Education, Preschool -- United States; Preschool teaching -- United States; Child development -- United States; Early childhood education -- United States